Survey of Afro-Asian literature - Cordova, Monique Escalada-; Uytico, Baby Jane (Quezon City : Lorimar Publishing Inc., 2024)
This book provides students a diverse selection of Afro-Asian literary pieces that are both meaningful and relevant to foster appreciation and understanding of the literary heritage that shapes their identity as Asians. It is designed to nurture critical and independent thinking by cultivating a mindful awareness of the social, political, economic, and cultural issues in the region. Through a variety of texts and tasks, literary theories, and lenses, learners will be able to deepen their knowledge of significant human experiences in order to cultivate and lead a meaningful life. There are nine lessons in this book, each focusing on the literature of the countries in Africa and Asia such as Egypt and Arabia, China, South Korea, Singapore, Indonesia, Myanmar, Japan, and Persia. The lessons are divided into several sections.
1. Africa: of Nature and Culture 1-11 -- 2. Egypt and Arabia : Tales of the Nile and Arabian Nights 12-21 -- 3. China: Red Dragon of the East 22-29 -- 4. The Literature of Korea 30-39 -- 5. The Literature of Singapore 40-46 -- 6. The Literature of Indonesia 47-52 -- 7. The Literature of Myanmar 53-59 -- 8. Hebrew and its Stories Past 60-65 -- 9. Stories of the Land of Ayans 66-70 .
Includes bibliographical references.
Keywords: LITERATURE; ASIA AFRICAN LITERATURE